Effect of herbal products and their active constituents on angiogenesis in diabetic wounds - Herman, Anna (Planta Medica)
Angiogenesis plays a key role in tissue regeneration by delivering oxygen and nutrients to the injury site. In diabetes mellitus, various factors, including hyperglycemia, neuropathy, increased reactive oxygen species, and proinflammatory cytokines, decrease the levels of proangiogenic factors, and increase levels of antiangiogenic factors, hamper angiogenesis and hinder wound healing. Reconstruction of the vasculature of the wound bed is crucial for promoting diabetic wound healing and improving the quality of life of patients. Given the urgent need for innovative therapies to promote angiogenesis and accelerate the repair of diabetic wounds, researchers have increasingly focused on identifying herbal products and their active constituents with promising proangiogenic activity. The aim of this review is to present verified data on the current knowledge on the effect of herbal products and their active constituents on angiogenesis processes in diabetic wounds. The electronic databases were searched for articles published from 2014 to present. The 38 articles comparing topically used herbal products /active constituents on angiogenesis in diabetic wound healing treatment versus control treatments (placebo or active therapy) were selected. Herbal products and their active constituents are rich sources of novel angio-modulators that may affect the angiogenesis process in diabetic wound healing via different mechanisms of action, including stimulation of VEGF, HRMs and activation of the Nrf2, PI3K/AKT, and HIF-1α signaling pathways. Topical applications of herbal products and their active constituents, especially when incorporated into wound dressings, show promising proangiogenic activity and represent a potential alternative for the treatment of diabetic wounds.